Hypertension knowledge and treatment initiation, adherence, and discontinuation among adults in Chennai, India: a cross-sectional study - Sudharsanan, Nikkil; Ali, Mohammed K.; McConnell, Margaret A. (BMJ open, 2021)
Introduction A substantial share of urban Indians with diagnosed hypertension do not take regular treatment, potentially due to poor knowledge of hypertension consequences and treatment options. We describe hypertension knowledge and beliefs, treatment patterns, and reported reasons for treatment non-use among adults with diagnosed hypertension in Chennai, India. - Methods We collected data on 833 adults ages 30+ with physician diagnosed hypertension using a door-to-door household survey within randomly selected wards of Chennai. We described the proportion of individuals who were not taking daily medications and their reported reasons for not doing so. Next, we described individuals’ knowledge of hypertension consequences and how to control blood pressure (BP) and assessed the association between knowledge and daily treatment use. - Results Over one quarter (28% (95% CI 25% to 31%)) of diagnosed individuals reported not taking daily treatment. The largest proportion (18% (95% CI 16% to 21%)) were individuals who had discontinued prior treatment use. The primary reason individuals reported for non-daily use was that their BP had returned to normal. Just 23% (95% CI 20% to 26%) of individuals listed BP medications as the most effective way to reduce BP; however, these individuals were 11% points (95% CI 4% to 19%) more likely to take daily medications. Conversely, 43% (95% CI 40% to 47%) of individuals believed that BP medications should be stopped from time to time and these individuals were 15% points (95% CI −0.21 to -0.09) less likely to take daily treatment. While awareness of the consequences of hypertension was poor, we found no evidence that it was associated with taking daily medications. - Conclusions There were large gaps in consistency of BP medication use which were strongly associated with knowledge about BP medications. Further research is needed to identify whether addressing beliefs can improve daily treatment use among individuals with diagnosed hypertension.
Gesehen am 06.05.2022